Legal Analysis of Residential Tenancy Permits Overruling Right of use Certificates in Light of Pmk No. 115/Pmk.06/2020 - Sigit Mustika, I Komang; Karsoma, Ateng; Jaeni, Ahmad (Institute for Law and Economics Studies, 2025)
State Houses or Official Residences are also classified as State Property, all of which are legally obtained from the State Budget. Members of the Indonesian National Armed Forces (TNI) who are granted Official Residences must maintain and preserve the buildings so that the utilization of State Property can carry out all TNI duties and functions without changing the ownership status. This is in accordance with TNI Commander Regulation No. 49 of 2015 concerning the Utilization of State Property in the form of land and buildings within the TNI. The type of research used in this thesis is normative juridical research. Normative juridical research examines the law from an internal perspective, with the object of research being legal norms. The approaches used are the legislative approach, the conceptual approach, the case approach, and the comparative approach with several countries. The results of this study show that the Occupancy Permit (SIP) is essentially a temporary administrative permit, so it cannot be equated with land rights such as a right-of-use certificate. Therefore, legally, a right-of-use certificate has greater legal force than an SIP. However, in practice, there is often a conflict between legal certainty (certificates) and the sense of justice of the community (long-term residents with SIPs). This happened because the residents had occupied the official residences for a long time and felt they had moral and historical rights to the dwellings. The court's decision affirming the validity of the right-of-use certificates reflects a positive legal orientation that emphasizes legal formalities over sociological aspects.